Student engagement during pandemic COVID-19 and its implications for guidance and counseling - Nugroho, Imam Setyo; Kusumawati, Eny; Wahyuningsih, Diana Dewi (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2021)
Student engagement is a condition of the extent to which students play an active role in the learning process by focusing on time, energy, mind, effort, feelings and making it happen in action to complete their academic tasks completely. This study aims to explore and find out the level of student engagement in the Covid-19 pandemic period seen from gender differences and the school level. Quantitative descriptive research with this survey design involves 469 students, 245 students of the junior high school, and 224 senior high school students chosen using a stratified random sampling proportionate cluster. The results showed that secondary school students in the Covid-19 pandemic period had an average level of student engagement in the medium category. This study found, there was no different level of student engagement based on gender (t (467) = -1.86). But specifically, the participation has a significant difference, while the skill, emotion, and performance do not have a significant difference. At the school level, indicate that there are significant differences in the level of student engagement (t(467)= -3.39). Furthermore, it can be seen from every indicator of student engagement skills, participation and performance have a significant difference and only an emotion that does not have it. The results of this study have implications for the planning of guidance and counseling programs in schools during the Covid-19 pandemic period, which is important to see the level of student engagement, especially in the emotional indicator. Further discussion is discussed in this article.